PENILAIAN DAMPAK BIODIVERSITAS LAUT (KASUS GUGUS PULAU BATUDAKA PROVINSI SULAWESI TENGAH) - Dwi Sulistiawati; Luky Adrianto; Ismudi Muchsin; Abdul Masyahoro (Bumi Lestari Journal of Environment, 2012)
The need better understand the linkages and interdependencies of socio-economic and coastal environmental dynamics has taken on a more deliberate role in the development and assessment of Integrated Coastal Management on Batudaka islands. The DPSIR (drivers- pressures - states - impacts - responses) framework was used in scoping biodiversity management issues and problems. DPSIR model is to analyze the causative factors of pressure on the ecosystem of small islands and recommendations for environmental restoration effort. Results of the study showed that population and economic (tourism and fisheries demand) driving forces causing ecosystem vulnerable.  Land conversions, domestic waste, other pollutant was pressured this area, while increasing driving forces. The State environmental as waters quality is still relative well for tourisms and fisheries activity, physical impact as abrasion and sedimentation, habitat loss and biodiversity changes at 2000 until 2010 year at Batudaka Islands increase life coral and mangrove, decrease seagrass. Impact to environment  i.e. water abstraction,  sediment water fluxes across  coastal zones, change of habitats and biological diversity can be caused decreasing of coastal ecosystem. Functional diversity can be defined as a variety of different responses to environmental change, in particular the variety of spatial and temporal scales with which organisms reach to each other and to the environment. The policy objective of maximum